Optimasi Kecerdasan Buatan di Rumah Tangga Untuk Meningkatkan Efisiensi Melalui Metode Otomatisasi - Abdurrobi Elman Sudri; Anggelia Wijayanti; Azis Firdaus; Sabila Fatimah Azzahra; Aries Saifudin (CV. Shofanah Media Berkah, 2024)
Artificial Intelligence (AI) is gaining increasing popularity in household applications, promising to enhance efficiency and comfort in daily life. This article discusses AI optimization strategies in the home environment with a focus on improving efficiency. This research proposes a novel method that combines machine learning and cloud computing to improve the accuracy and efficiency of AI tasks in households. Research results demonstrate a significant reduction in the time and resources required to complete these tasks.